The United Republic of Tanzania : Decentralisation Sector Work - World Bank (Washington, DC, 2013)
The primary objectives of the Tanzania Decentralization Sector Work (DSW) are: To develop a strategic analysis of the decentralization process in Tanzania, commonly known as the Local Government Reform Programme (LGRP); and on this basis, to formulate proposals regarding a) the orientation of the World Bank towards the LGRP and the modalities of the Bank's potential involvement in the Programme, and b) appropriate responses by the Bank at the project level in those sectors affected by the LGRP. The DSW is intended to enhance the Bank's understanding of developments in the decentralization theme area and to optimize Bank decision-making regarding its involvement here. It also aims to assist the Bank in structuring its projects such that the impact of the decentralization process is taken into proper account.